Dysprosody in three patients with vascular cerebral damage - Pietrosemoli, Lourdes; Mora Gallardo, Elsa (My University, 2011)
The data on the neurological bases of prosody are apparently contradictory. This has led to the postulation of four different hypotheses about the cerebral organization of prosody. In the present study the rhythm and melodic contours of spontaneous speech are analyzed for two patients with vascular damage in the right hemisphere and for one in the left hemisphere. The acoustic analysis demonstrated some prosodic problems with relation to intonation but more with rhythm. These data reinforce the hypothesis of bilateral control of prosody and suggest the intervention of sub-cortical areas. They also contribute to the rejection of the organizational model of prosody in the right hemisphere as parallel to the linguistic organization in the left hemisphere.
Keywords: Departamento de Lingüística; Escuela de Letras; Facultad de Humanidades y Educación; Artes y Humanidades; Artículos; Centro de Investigación y Atención Lingüística "Julio Cesar Salas" (CIAL)